Penny Postcard of the Carnegie Library of Oxnard, CA - United States Post Office::::::
Penny postcard image of the Carnegie Library, built in Oxnard, CA in 1907. The library was converted and remains an art museum. Image digitized by Broome Library, California State University Channel Islands. Original 35mm slide housed at E.P. Foster Library, Ventura, California.